Evaluating Educational Innovation: Insights from Integrative STEAM Projects in Jordan - Zaitoun, Eman; Nazzal, Samar; Zaitoun, Asma; Ayyad, Suraya (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
This study aims to evaluate these projects and inform future design, teacher training, and practice evaluation in Jordan.